Signage dan Penerapannya: Lingkungan Jalan Raya Tol Bintaro - Puspitasari, Dyah Gayatri; Darmawan, James (Bina Nusantara University, 2013)
The term ‘signage’ sometimes has been confused with the term ‘sign or symbol’, although the term signage is actually a theme which has consistency and also covers an area from a specific environment and mood. Signage has been designed to inform about location and direction of interior and exterior environment. In general, design system and the use of signage, such as graphic standard, material and the positioning, has been organized by international standardization from every country in the world. One of the most important categories of signage is the application of signage in highways. The study is about signage from historical background, category, color scheme, design and human factor approach; from psychological physics, social culture, to the connectivity with the value and products’ characteristic. Human factor comprehension is also one of the most important elements in signage design process. Each perspective or perception from highway user and their reaction about the signage has been conditioned by a specific characteristic of human, such as from biophysics-psyche, socio-culture, spiritual cosmologis transcendental with its five senses. Human factor as a user has an important role to obtain the best solution or good design solution for the community who use that signage.